2019
DOI: 10.1186/s12913-019-4535-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and barriers of outpatient diabetes care in rural health facilities in Uganda – a mixed methods study

Abstract: Background Despite the increasing burden of diabetes in Uganda, little is known about the quality of type 2 diabetes mellitus (T2DM) care especially in rural areas. Poor quality of care is a serious limitation to the control of diabetes and its complications. This study assessed the quality of care and barriers to service delivery in two rural districts in Eastern Uganda. Methods This was a mixed methods cross-sectional study, conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…Increasing screening will inevitably place a greater burden on the health system to provide medications and clinic visits to more individuals. This will put additional stress on an already under-performing system [ 8 , 9 ]. However, leveraging pre-existing HIV infrastructure as was done in this study already has been shown to be feasible and cost-effective when tailored to the appropriate population [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing screening will inevitably place a greater burden on the health system to provide medications and clinic visits to more individuals. This will put additional stress on an already under-performing system [ 8 , 9 ]. However, leveraging pre-existing HIV infrastructure as was done in this study already has been shown to be feasible and cost-effective when tailored to the appropriate population [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 80% of Ugandan health facilities offered blood glucose testing and 34% offered diabetes management in 2013 [ 8 ]. Rural clinics in Uganda continue to face challenges in training health workers and providing continuous support for diabetes care [ 9 ]. Additionally, the Ugandan essential medicines list includes medications for hypertension and diabetes management [ 10 , 11 ], but there is limited availability of essential medicines throughout Uganda and there are disparities related to less access at public hospitals compared to private for-profit hospitals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 16 Lack of HbA1c tests in health care facilities is one of the hindrances for clinicians to make long-term management decisions about DM patients. 17 Reports also showed that the absence of HbA1c measurement was an important indicator of frequent hospital readmission in T2 DM patients. 18 , 19 Moreover, it has been reported that limited access to the HbA1c test appeared to be a key predictor of poor glycemic control and is a significant obstacle to improving glycemic control in T2 DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, about half of all individuals with diabetes and 9 in 10 of those with impaired fasting glucose are unaware of their status [10]. Diagnostic services are heavily constrained as critical diagnostic equipment are lacking, reagents are in short supply, and healthcare workers' training on diabetic care is limited [11][12][13]. The pathways to diabetes diagnosis has not been well elaborated in Uganda, which undermines efforts to improve diagnostic processes.…”
Section: Introductionmentioning
confidence: 99%